HLA-DR genotype risks in seropositive rheumatoid arthritis. - Legrand, L (1984)
We studied the distribution of HLA-A, B, C, and -DR antigens in 77 Caucasian patients with sero-positive rheumatoid arthritis. Forty-four patients were genotyped and compared with the control panel of 110 unrelated Caucasian genotyped donors. The data obtained confirm the association of DR4 with RA, and reveal an increased risk of disease for patients carrying DR1, DR2, and DR3, compared to the risk for those carrying other antigens, such as DR5, DRw6, and DR7. There is a higher risk for DR4/4 homozygotes than for DR4/1, DR4/2, or DR4/3 heterozygotes. DR4/5, DR4/6, and DR4/7 have a lower risk than the previously mentioned genotypes. The genotype risks are compatible with the inheritance of a single, linked genetic determinant of disease susceptibility, but we are unable to distinguish between recessive and dominant inheritance of susceptibility using the "antigen-frequencies-amongst-diseases" method. DR4 seems to be more frequent in patients in whom onset occurs before the age of 35 (79% vs. 54% DR4 positive). A significant excess of DR3 + is observed in patients with toxic complications following treatment with gold salts (X2(1) = 8.96).